Perkembangan Usia Lanjut - Zaskya Rahmadani; Intan Yulia Putri; Linda Yarni (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
The development of old age is a phase of life characterized by various physical, cognitive, emotional and social changes in aging individuals. This phase involves adjusting to new challenges, such as declining physical function and health requiring intensive care. Apart from that, there are also changes in cognitive abilities such as memory and thought processes. Emotional and social aspects also undergo evolution with adjustment to new social roles and the loss of people close to them. This research aims to analyze and understand the dynamics of development in old age and its implications for an individual's quality of life.